Intertextuality in Marchella Fp's Novel, “Nanti Kita Cerita Tentang Hari Ini” and Almira Bastari's Novel, “Home Sweet Loan” - Dwi Septiani, Alika; Agi Ahmad Ginanjar (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes the intertextual relationship between Marchella F. P.’s Nanti Kita Cerita Tentang Hari Ini (NKCTHI) and Almira Bastari’s Home Sweet Loan (HSL), two contemporary Indonesian novels that highlight family dynamics, psychological wounds, and social pressures on younger generations. Using Julia Kristeva’s concept of intertextuality, the study positions NKCTHI as a hypogram that is thematically and contextually transformed in HSL. The analysis covers intrinsic elements (theme, characters, plot, point of view, style) and extrinsic elements (social, psychological, and cultural values). The findings reveal that although NKCTHI adopts a poetic-reflective style while HSL employs a light-satirical tone, both depict family as a site of conflict and emotional wounds. Intertextuality emerges in the portrayal of children’s alienation within their own homes and the socio-cultural expectations imposed on their roles in urban families. The study concludes that the two novels are interconnected not only in narrative and theme, but also in their function as literary reflections of intergenerational trauma and as mediums for readers to understand the importance of emotional reconciliation within families.